104: PERIOPERATIVE STRATEGIES IN ESOPHAGEAL CANCER RESECTION IN 12 NORDIC UNIVERSITY HOSPITALS. (23rd April 2022) - Achiam, M P; Nilsson, M; Åkesson, O; Johansson, J; Edholm, D; Lindblad, M; Szabo, E; Sundbom, M; Lindberg, F; Bau Mortensen, M; Kjus Aahlin, E; Mala, T; et al.
Abstract: Background and aim: The Nordic countries have similar health care systems and registries simplifying epidemiological research. Differences in treatment traditions can, however, hamper the possibility to assess results and to harmonize control arms in joint randomized trials. In the process to set up a Nordic multi-center randomized trial regarding use of nasogastric tube (NG-tube) decompression after esophagectomy, we aimed to investigate perioperative routines in 12 University Hospitals in Sweden, Denmark, Norway and Finland. Methods: All Nordic University Hospitals were contacted regarding a Nordic randomized controlled trial exploring effects and complications associated with the use of nasogastric tube use after esophagectomy for cancer. Those who chose to join the trial were sent a questionnaire regarding surgical and perioperative routines. Results: Twelve centers with a combined catchment area of 16 million inhabitants and an annual volume of 400 esophagectomies joined the trial network. All but one used totally minimally invasive or hybrid surgical approach. All 12 centers reported routine use of NG-tube and 5 employed continuous suction. The NG-tube was removed between 3 and 7 days postoperatively. A routine pylorus drainage procedure was reported from two centers. Jejunostomy was used universally in 5 centers and selectively in 6 centers. One center did not use jejunostomy. Conclusion: Differences in perioperative care after esophagectomy is apparent in the Nordic countries, highlighting the need for high-level evidence regarding these practices. A unified approach may facilitate clinical trial initiatives. There is a paucity of evidence regarding optimal NG-tube use after esophagectomy for cancer and a randomized trial investigating this issue is under way.